Math, asked by Empror, 6 months ago

Using the remainder theorem show that when the polynomial p(x) = 3x^3 + 14x^2 - 2x - 15 is divided by (x-1), the remainder is zero. What do you infer?

If answered correctly I will mark you brainlyeast answer

Answers

Answered by khushisathish100
1

Answer:

-28

Step-by-step explanation:

x-1=0

x=1

3-14-2-15

=-28

Answered by ujjwal26200
1

Answer:

Answer:

-28

Step-by-step explanation:

x-1=0

x=1

3-14-2-15

=-28

Step-by-step explanation:

Similar questions